A Minimal Dynamic Structure Model Considering Dry Friction Energy Dissipation in Refrigerant‐Lubricated Gas Foil Bearings. Issue 1 (15th March 2018) - Leister, Tim; Bard, Sebastian; Seemann, Wolfgang
Abstract: In the simulation of gas foil bearing rotor systems, computational time is considered a highly critical aspect. Consequently, a great number of sophisticated foil structure models found in literature reveal to be inapplicable for a fully coupled analysis of the overall system's nonlinear dynamic response. On the other hand, most notably if considering heavily loaded bearings, phenomena such as dry friction within the foil structure cannot be neglected without introducing substantial inaccuracies. To overcome these limitations, the minimal dynamic structure model described in this contribution considers a regularized Coulomb friction law applied to a reduced spring–mass arrangement. After the successful validation against static FE results, a transient simulation is carried out, allowing for interesting insights into the mechanisms behind beneficial energy dissipation. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)